ANALISIS USAHA TANI DAN STRATEGI PEMASARAN BUAH BELIMBING MANIS DI DESA KALIBENING KABUPATEN MUSI RAWAS - Febrina Nur Annisa; Ira Primalasari (JURNAL CITRA AGRI TAMA, 2023)
In Kalibening Village,Musi Rawas District, the community has a high need for the star fruit cultivation industry. The purpose of this study was to evaluate starfruit cultivation and promotion methods used in Kalibening Village Musi Rawas District, The literature study method was used in this study. According to the findings of the study, one harvest of star fruit yields a total profit of IDR 5,039,094 after deducting the total production cost (IDR 4,412,938) of the total production and farm income (IDR 9,452,031). In Rawas District, there are three different ways to market star fruit. Carambola was originally sold by farmers directly to consumers. On the main road, sales of starfruit take place. Second, retailers buy products from farmers directly and resell them to customers. Third, star fruit will be distributed to retailers by wholesalers. Carambola then reaches consumers from retail traders. Keywords: starfruit, farming, marketing